Market Structure and Market Performance of Tuna Value Chain: A Case Study of Yellowfin Tuna and Bigeye Tuna Value Chain in Three South Central Provinces of Vietnam - Thu, Nguyen Dang Hoang; Quyen, Cao Le; Hang, Le Thi Minh; Thi, Nang Thu Tran; Lebailly, Philippe (International Journal of Economics and Financial Issues, 2021)
A value chain integrated Structure Conduct Performance (SCP) framework applied in agribusiness products in general and fishery products, in particular, is of great significance in conceptualizing strategy design specifically to a value chain segment in a territory in terms of economic development. This study analysed the market structure and financial performance of each actor in the tuna value chain in three South Central provinces of Vietnam to provide an overview of the economic efficiency of the value chain. We interviewed 315 respondents, including shipowners, middle-persons, and processors, directly related to the tuna value chain in 2018. The market concentration of each actor was quantitatively determined by the Lorenz curve and Gini coefficient. Actor’s financial performance was calculated by costs and earnings models. The results showed that the market structure of middle-persons and processors tended to be monopolistic while shipowner’s market structure tended to be in perfect competition. The processors received the highest return compared to other actors due to their highest value-added contribution and the most significant business scale. Several policy interventions were suggested to improve the economic efficiency of the value chain. Keywords: Market Structure, Market Concentration, Market Performance, Tuna Value Chain, Vietnam. JEL Classifications: M, Q, R DOI: https://doi.org/10.32479/ijefi.11911